Use Of Music On City Transport Routes Pasar – Simpang Rimbo Jambi City - Ramadhanti, Sri (UNIVERSITAS PAKUAN, 2023)
The variety of passengers on the Pasar – Simpang Rimbo route allows drivers to play various types of music, so the music played by the Driver does not provide comfort for passengers. The research method in this study is qualitative, and the aim is to get an overview or representation of several types of music that are predominantly played in City Transport - City Transport, the function of music in City Transport, and the influence of music on the Driver and passengers of City Transport Pasar - Simpang Rimbo route. The data obtained will be analyzed using the Miles and Huberman data analysis model. The results showed that three types of music are predominantly played on public transportation routes: Pasar – Simpang Rimbo, namely Disco or RnB music, Indonesian Pop music, and Western Pop. Then, some of the functions of music in public transportation are as a means of emotional expression, as entertainment, and as a physical reaction. Listening to music influences pleasure and benefits and affects the Driver's condition and the Passenger's mood.